The effect of the implementation of the Learning Start with a Question (LSQ) learning strategy on the learning outcomes of economics students in class X at MA Muhammadiyah Pekanbaru - Putri , Asri Neli; Rambe, Paijan; Suparmi, Suparmi; Ningsih, Sukma Setia; Amin, Syahrul (LP3M Universitas Islam Zainul Hasan Genggong, 2024)
This study aims to find out whether there is a difference in learning outcomes after applying the Learning Start With A Question (LSQ) learning strategy to student learning outcomes in financial institutions (banks) in Economics in class X MA Muhammadiyah Pekanbaru. The subjects in the study were 33 students. Data collection was carried out from posttest questions given to students in the control class and experimental class. The learning outcomes obtained when conducting research were an average score of 71.76, while for the experimental class the average score was 76.25. Thus, the average score obtained from the experimental class that was treated in the form of LSQ strategy was higher than that of the control class that was not treated. In the normality test, the data obtained was not normal, so the researcher processed the data using a non-parametric test obtained the hypothesis that the processed value was 0.601>0.05, indicating that Ha was rejected and H0 was accepted. This means that there is no significant average difference between the use of LSQ and conventional learning strategies.